Desain UI/UX Aplikatif Telemedicine Dalam Optimalisasi Rekam Medis Elektronik Di Puskesmas X Bengkulu Utara - Ridhatul Adilla Nur Dhani, Wafiq; Larasati, Sarah; Sary, A'idah Haniyah (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Manual medical record management at Puskesmas X Bengkulu Utara faces constraints on efficiency, risk of damage, and data accuracy. Electronic Medical Records (EMR) are a transformative solution, improving operational efficiency and service quality. Telemedicine, which enables remote healthcare services, can integrate with EMR for seamless data exchange and increased accessibility. However, the transition to this digital system is faced with the challenges of poor user interface (UI) and user experience (UX) design, which can hinder adoption by medical personnel. This study emphasizes the design of functional and intuitive UI/UX, adopting User-Centered Design (UCD). The process involved needs analysis, persona creation, and visual design using Figma. The visual design took into account aesthetics and cognitive psychology, such as the dominance of light blue and white for a professional impression, easy-to-read sans-serif typography, and a consistent grid-based layout. Specifically, the design addressed the issue of multiple forms by introducing a Floating Action Button (FAB) as a single dynamic entry point for data input. The FAB would trigger a contextual input interface, adjusting input options based on the feature the user was accessing. The consistent structure of the health feature pages also ensured a recognizable workflow. This approach reduced confusion, prevented data duplication, and improved data integrity. The transition from â€œmultiple formsâ€ to â€œone dynamic inputâ€ through this cohesive design significantly improved the user experience (UX), driving efficiency and long-term engagement in healthcare services at Puskesmas X Bengkulu Utara.